Analysis Of The Implementation Of The Child Pneumonia Management Program At Paal V Health Center, Jambi City In 2023 - Viska Andini; Adila Solida; Kasyani, Kasyani; Dwi Noerjoedianto; Silvia Mawarti Perdana (Sean Institute, 2024)
Background: Pneumonia is a type of Acute Respiratory Infection (ARI) that has been a cause of death for 740,180 children under 5 years old in 2019, constituting 14% of total deaths in children under five, but reaching 22% of all deaths in children aged 1 to 5 years. The objective of this study is to analyze the implementation of the pneumonia management program at Paal V Health Center in Jambi City. Method: This study uses a qualitative research approach with an analytical design, gathering data through a survey of health workers conducted by the author at Paal V Health Center in Jambi City. Research informantts consist of 8 key informantts, including 1 Program Coordinator for Pneumonia at Paal V Health Center, 1 Head of Paal V Health Center, 2 implementing officers, and 4 mothers of children with pneumonia. Results: The research findings indicate that Paal V Health Center has two health workers, which is inadequate for managing pneumonia cases. Infrastructure is not up to standard, primarily due to the absence of nebulization equipment. Planning and program implementation are generally good with counseling and record-keeping, but there are shortcomings in providing written information to mothers about follow-up appointment schedules. Regular monitoring and evaluation are conducted by health workers and the head of the health center. Conclusion: The management of pneumonia cases at Paal V Health Center is suboptimal due to limited healthcare personnel and equipment. With additional resources and improved communication, pneumonia management can become more effective and efficient.